Fluorine-expedited nitridation of layered perovskite Sr2TiO4 for visible-light-driven photocatalytic overall water splitting - Jinxing Yu; Jie Huang; Ronghua Li; Yanbo Li; Gang Liu; Xiaoxiang Xu (Nature Communications)
Abstract Photocatalytic overall water splitting is a promising approach for a sustainable hydrogen provision using solar energy. For sufficient solar energy utilization, this reaction ought to be operated based on visible-light-active semiconductors, which is very challenging. In this work, an F-expedited nitridation strategy is applied to modify the wide-bandgap semiconductor Sr2TiO4 for visible-light-driven photocatalytic overall water splitting. Compared to the conventional nitridation approach, F-expedited nitridation introduces the desirable integration of a high concentration of N dopant for strong visible light absorption and a low concentration of defects (i.e. Ti3+ and oxygen vacancies) for effective separation of photocarriers. After being coated with Ti-oxyhydroxide protection layer and deposited with RhCrOy cocatalyst, the product from F-expedited nitridation can stably run photocatalytic overall water splitting with apparent quantum efficiency of 0.39% at 420 ± 20 nm and solar-to-hydrogen efficiency of 0.028%. These findings justify the effectiveness of F-expedited nitridation strategy and serve as a guidance to upgrade the photocatalytic activity of many other wide-bandgap semiconductors.